2018
DOI: 10.1098/rsos.180491
|View full text |Cite
|
Sign up to set email alerts
|

Goats prefer positive human emotional facial expressions

Abstract: Domestication has shaped the physiology and the behaviour of animals to better adapt to human environments. Therefore, human facial expressions may be highly informative for animals domesticated for working closely with people, such as dogs and horses. However, it is not known whether other animals, and particularly those domesticated primarily for production, such as goats, are capable of perceiving human emotional cues. In this study, we investigated whether goats can distinguish human facial expressions whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 47 publications
3
43
0
2
Order By: Relevance
“…Moreover, dogs and horses show a functional understanding of human emotional signals and adjust their behavior according to the valence and intensity of the emotional message conveyed [ 11 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. Similar results have been recently reported by Nawroth and colleagues for goats, which discriminate human facial expression of anger and happiness and prefer to interact with the latter [ 60 ]. Studies on cats showed that they are sensitive to conspecific and human emotional signals, though to a lesser extent than dogs [ 10 , 42 , 50 ].…”
Section: Introductionsupporting
confidence: 90%
“…Moreover, dogs and horses show a functional understanding of human emotional signals and adjust their behavior according to the valence and intensity of the emotional message conveyed [ 11 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. Similar results have been recently reported by Nawroth and colleagues for goats, which discriminate human facial expression of anger and happiness and prefer to interact with the latter [ 60 ]. Studies on cats showed that they are sensitive to conspecific and human emotional signals, though to a lesser extent than dogs [ 10 , 42 , 50 ].…”
Section: Introductionsupporting
confidence: 90%
“…Although beyond the scope of this article, these human factors should be considered when thinking of the HAR. There is also increasing evidence that animals can recognize human facial expression of emotions [dog ( 149 151 ), horse ( 152 ), goat ( 153 )] or human bodily expression [cat ( 154 )] and prefer positive human emotional expressions.…”
Section: Implications For Practicementioning
confidence: 99%
“…Goats integrate visual and auditory cues to identify herd mates, especially for social partners ( Pitcher et al, 2017 ), indicating higher-order cognitive representations of individuals. Domesticated goats can distinguish between positive and negative human facial expressions ( Nawroth et al, 2018 ), can distinguish between different shapes, or can track the movement of objects (reviewed by Nawroth [2017] ). Goats can successfully categorize similar symbols and generalize to new symbols ( Meyer et al, 2012 ) and can identify a symbol that did not belong to a group; these abilities were previously attributed only to primates ( Roitberg and Franz, 2004 ).…”
Section: Natural Behavior Of Goatsmentioning
confidence: 99%